A guide to orthophotographic surveying using photogrammetry as applied to archaeological heritage from the choice of tools to process settings within the open-source software MicMac (IGN ENSG) - Verriez, Quentin (Annales littéraires, 2023)
If the uses of photogrammetry are many and various, the use of it in archaeology is now well standardised in the large majority of these uses. It is mainly a replacement of the traditional plan, section and elevation measurements of archaeological remains by the production of ortho-images, known as orthomosaics. This guide aims to provide students and professionals of our discipline with a complete protocol (from field acquisition to data storage), which has been tried and tested, with reproducible results, and which is entirely based on free scientific tools.